Explaining Religion (Away?) - Jong, Jonathan (Sophia, 2013)
In light of the advancements in cognitive science and the evolutionary psychology of religion in the past two decades, scientists and philosophers have begun to reflect on the theological and atheological implications of naturalistic—and in particular, evolutionary—explanations of religious belief and behaviour. However, philosophical naiveté is often evinced by scientists and scientific naiveté by philosophers. The aim of this article is to draw from these recent contributions, point out some common pitfalls and important insights, and suggest a way forward. This proposal avoids the genetic fallacy as well as misunderstandings of the cognitive mechanisms that give rise to religious belief. In the end, it may well be that the cognitive science of religion is atheologically and theologically ambiguous; traditional philosophers of religion on both sides of the debate still have work to do.